2003
DOI: 10.1007/s00702-003-0077-8
|View full text |Cite
|
Sign up to set email alerts
|

cDNA gene expression profile of rat hippocampus after chronic treatment with antidepressant drugs

Abstract: A significant number and homology in gene expression were observed with the three antidepressants. Many of the genes were associated with neurogenesis and synaptogenesis, including synaptophysin and neogenin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…Not surprisingly, a significant majority of upregulated genes were associated with neurogenesis and/or synaptogenesis: these include factors known to promote the proliferation of neuronal progenitor cells (Npy, Edg3, Lgals1, Serpinf1/Pedf, Hspb1), growth factor-associated genes involved in survival and differentiation of adult neuronal cells (Bdnf, Inhba, Acvr1c, c-Ret), and downstream immediate early genes (IEGs) and transcription factors (c-fos, Sox11, Egr3, S100a6). Among the downregulated genes were Calb1, a marker of mature granule neurons, Prdm5, which has growth-suppressive (Khawaja et al, 2004) and amitriptyline, moclobemide, and clorgyline (Drigues et al, 2003). The present microarray results support the hypothesis that BDNF and other growth factors play an important role in antidepressant activity.…”
Section: Discussionsupporting
confidence: 80%
“…Not surprisingly, a significant majority of upregulated genes were associated with neurogenesis and/or synaptogenesis: these include factors known to promote the proliferation of neuronal progenitor cells (Npy, Edg3, Lgals1, Serpinf1/Pedf, Hspb1), growth factor-associated genes involved in survival and differentiation of adult neuronal cells (Bdnf, Inhba, Acvr1c, c-Ret), and downstream immediate early genes (IEGs) and transcription factors (c-fos, Sox11, Egr3, S100a6). Among the downregulated genes were Calb1, a marker of mature granule neurons, Prdm5, which has growth-suppressive (Khawaja et al, 2004) and amitriptyline, moclobemide, and clorgyline (Drigues et al, 2003). The present microarray results support the hypothesis that BDNF and other growth factors play an important role in antidepressant activity.…”
Section: Discussionsupporting
confidence: 80%
“…32,33 Nsf 34 and synaptotagmin 1 35,36 have both been implicated in the regulation of neurotransmitter release. Crispino et al 37 described a modulation of Syt1 mRNA levels in area CA3 of the hippocampus during the estrous cycle with highest levels occurring during diestrus, while Jenkins et al 38 showed that rats in diestrus were more vulnerable to develop LH, thus supporting our observations that lowered levels of Syt1 are accompanied by increased stress resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches have been previously used to investigate the molecular alterations induced by ADs in the hippocampus and other brain regions of naive animals (Conti et al, 2007;Gaska et al, 2012;Korostynski et al, 2013;Landgrebe et al, 2002;Lee et al, 2010;Sillaber et al, 2008;Surget et al, 2009;Takahashi et al, 2006); interpretation of these studies is, however, limited by the fact that treatment of individuals who do not display signs of depressive-like behavior is not comparable to a pathological context (Cryan and Slattery, 2007). Previous comparable studies relied on measures of a single behavioral index measurement (Drigues et al, 2003;Nakatani et al, 2004), while others using multidimensional animal models of depression focused on a single class of AD (Andrus et al, 2012;Datson et al, 2012;Lisowski et al, 2013;Surget et al, 2009) or two monoaminergic ADs (Malki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%